Análisis comparativo entre los equipos de medición RTK Real Time Kinematic y estación total, realizando un levantamiento en la comuna de Engabao - Carriel Gutiérrez, Mario David (2024)
The text addresses a comparative analysis between two topographic technologies: the RTK (Real Time Kinematic) System and the Total Station. The RTK, which uses GNSS receivers, delivers real-time data with high accuracy, while the Total Station, an optical-electronic instrument, has been a reliable choice for accurate measurements. The purpose of the study is to evaluate which of these technologies is most suitable in different field conditions and specific contexts. Objectives include evaluating the accuracy of both technologies, managing costs in field work, and drawing up drawings for comparison. The hypothesis states that the comparison of the altimetry and planimetric results of both tools will determine their applicability in civil engineering, ensuring that the results meet the necessary requirements for an accurate topographic survey.